Numerical Feedback Stabilization with Applications to Networks. (22nd May 2017) - Göttlich, Simone; Schillen, Peter
Abstract : The focus is on the numerical consideration of feedback boundary control problems for linear systems of conservation laws including source terms. We explain under which conditions the numerical discretization can be used to design feedback boundary values for network applications such as electric transmission lines or traffic flow systems. Several numerical examples illustrate the properties of the results for different types of networks.